KONTRUKSI EPISTEMOLOGI ILMU PENGETAHUAN - Maryani Maryani; Isropil Siregar; Ahmad Syukriss; Rita Sahara Munte (Jurnal Genta Mulia, 2024)
This article as a whole discusses the philosophy of science and the development of the epistemological construction of science. The construction of an epistemology of science is an in-depth effort to understand the nature, sources and limits of knowledge. Epistemology as a branch of philosophy plays a key role in detailing the process of understanding, forming and assessing knowledge. There is a close relationship between the philosophy of science and the development of science, because the philosophy of science has always been a benchmark in the development of science. The philosophy of science is the initial foundation for the formation of a developing scientific epistemology. Some developments in the epistemology of science cannot be separated from the well-developed foundation of the philosophy of science. The essence of modern science cannot be separated from the basics of the philosophy of science. Another factor that binds science is realism and idealism which are a strong basis for developing the construction of scientific epistemology in the era of modern civilization like now. Research methods are used to gain in-depth insight into document analysis. The analysis technique used is document study of previous research results that are related to the philosophy of science. Data collection was carried out by searching reading books, scientific journals published on Google Scholar, digital libraries and libraries. This research is very important to carry out because the philosophy of science is the mother of the development of existing science.